Beta Modulation Depth Is Not Linked to Movement Features - Tatti, Elisa; Ricci, Serena; Mehraram, Ramtin; Lin, Nancy; George, Shaina; Nelson, Aaron B.; Ghilardi, Maria F. (Frontiers in Behavioral Neuroscience, 2019)
Beta power over the sensorimotor areas starts decreasing just before movement execution (event-related desynchronization, ERD) and increases post-movement (event- related synchronization, ERS). In this study we determined whether the magnitude of beta ERD, ERS and modulation depth are linked to movement characteristics, such as movement length and velocity. Brain activity was recorded with a 256-channels EEG system in 35 healthy subjects performing fast, uncorrected reaching movements to targets located at three distances. We found that the temporal profiles of velocity were bell-shaped and scaled to the appropriate target distance. However, the magnitude of beta ERD, ERS and modulation depth, as well as their timing, did not significantly change and were not related to movement features.